Airplane Landing by the Curvilinear Glide Paths in Limits of the Border Trajectories Modelling Method - Voloshenyuk, D.A. (Управляющие системы и машины, 2017)
A new airplane landing method, that would correspond to the modern civil aviation requirements and assured ecological and economical level enhancement is considered. We present the generation method (calculation and construction) development and modeling of the virtual curvilinear airplane landing descending glide path in the limits of the border trajectories with sustaining of own individual, optimal vertical landing descending profile from flight level to the runway threshold.